The Development of an Innovative Sufficiency School Administration by Means of Participatory Action Research - Inchaikhao, Rossukhon; Kornphoung, Anucha; Chaemchoy, Sukanya (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
The objectives of this research were 1) to study an innovative efficiency school components by synthesizing relevant documents and research and interview 8 people who had experience on sufficiency schools or innovative schools, 2) to develop of an innovative sufficiency school administration in both preparation and operation, and 3) to evaluate innovative sufficiency school administration to the innovative school by lesson learned meeting from public-private partnerships, educators in sufficiency school, and student representatives. The results of the research were as follows: The components of the innovative sufficiency school administration consisted of 2 levels: school and classroom levels. There were 6 elements in school level: 1) Background of the school, 2) Strategic plan of the school, 3) Leadership of the school administrators, 4) Internal structure of ICT in school, 5) Government and community support, and 6) Organizational culture of school, and 6 elements in classroom level also: 1) Learning objectives, 2) Teachers’ roles, 3) Students’ roles, 4) Utilizing ICT, media and learning resources, 5) Networking, and 6) Multiplicative results. Results of the development of an innovative sufficiency school through participatory action research revealed that selecting a school as Learning Centre of the philosophy of sufficiency economy in Phitsanulok. The preparation step was started by establishing both teams of 21 researchers and 15 developers from volunteers. The most environment analysis results were consistent with the innovative sufficiency school components. The weakness analysis brought about the formulation guidelines and strategies of an innovative sufficiency school administration, respectively. The three main strategies were 1) ICT structure development for education, 2) learning management enhancement through PLC, and 3) active promotion of a Public-private partnership. The operational step was the implementation of the strategic plan to be the operational plan which found that projects and activities could be proceeded with identified schedule including some problems solved during operation. Evaluation results from development of an innovation sufficiency school were attained according to the setting criteria. The successful factors were leadership, partnership networking support, and sufficiency school components serving the fulfillment to an innovative sufficiency school.